The Effect of Squat Depth Jump Exercises on Heading in Putra Buana Club Players - Ilham, Imron; Kristina, Putri Cicilia; Putri, Siti Ayu Risma (PPSDP International Journal of Education, 2024)
This study aims to determine the effect of squat depth jump training on heading in Putra Buana Club players. The method in this research is an experiment with a one design group pretest-posttest design. The research variables are squat depth jump training, and heading. The population of this research is all Men’s Buana Club players. The sample for this research was Putra Buana Club players, totaling 27 people. Data obtained using test techniques. Test result data was analyzed using t-test statistics. The research results obtained an average heading of 4.18, which increased after participating in squat depth jump training to 8.33. Meanwhile, the results of hypothesis testing obtained t-count > t-table or 51.307 > 2.17, there was an increase after being given squat depth jump training on the heading of the Putra Buana Club players and it was accepted as correct.